Oxidative Dna damage in human esophageal cancer: clinicopathological analysis of 8-hydroxydeoxyguanosine and its repair enzyme. Issue 3 (1st April 2014) - Kubo, N.; Morita, M.; Nakashima, Y.; Kitao, H.; Egashira, A.; Saeki, H.; Oki, E.; Kakeji, Y.; Oda, Y.; Maehara, Y.
Summary: Both internal and external oxidative stresses act on DNA and can induce carcinogenesis. 8-hydroxydeoxyguanosine (8-OHdG ) is an indicator of oxidative stress and it leads to transversion mutations and carcinogenesis. 8-OHdG is excision-repaired by 8-OHdG DNA glycosylase (OGG1 ). The purpose of this study is to clarify the effect of oxidative DNA damage and repair enzymes on esophageal carcinogenesis. The levels of 8-OHdG and OGG1 were immunohistochemically evaluated in resected specimens, including squamous cell carcinoma (SCC ) in 97 patients with esophageal cancer. Higher levels of 8-OHdG in normal esophageal epithelium were associated with a higher smoking index ( P = 0.0464). The 8-OHdG level was higher in cancerous areas than in normal epithelia ( P = 0.0061), whereas OGG1 expression was weaker in cancerous areas than in normal epithelia ( P < 0.0001). An increase of OGG1 expression in normal epithelium was observed as 8-OHdG levels increased ( P = 0.0011). However, this correlation was not observed in cancerous areas. High OGG1 expression in the cytoplasm was related to deeper tumors ( P = 0.0023), node metastasis ( P = 0.0065) and stage ( P = 0.0019). Oxidative DNA damage, which is attributable to smoking as well as disturbances in DNA repair systems, appears to be closely related to esophageal carcinogenesis and its progression.